Penerapan Community Based Tourism dalam Mendukung Pengembangan Pariwisata Berkelanjutan pada Wisata Kuliner Kampung Pempek Tanggo Rajo Cindo Palembang - Maretha, Fetty; Aprini, Hidayah; Leisthari, Fepi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Culinary tourism, an integral part of tourism, offers unique experiences that allow tourists to experience and understand regional culture through its traditional food and beverages. One culinary destination in Palembang with the potential to attract tourists is the Tanggo Rajo Cindo Palembang Pempek Village. This potential has not been optimally utilized due to low community involvement, particularly in digital marketing through social media platforms such as Facebook, Instagram, and TikTok, which offer limited content. The community service program aims to improve the knowledge and skills of business owners in promoting their products to increase sales. The method used is collaborative, integrative, and participatory, with direct partner involvement. The activity was carried out in the Pempek Village. Before the pandemic, there were nine businesses, but now only six remain. Limited social media capabilities have impacted sales. Results show an increase in followers and content viewers across various platforms. This increase is expected to help UMKM promote their products and encourage the implementation of Community-Based Tourism to support sustainable culinary tourism in Palembang.